Road to Net Zero Strategic Pathways for Sustainability-Driven Business Transformation - Zipse, Oliver; Hornegger, Joachim; Becker, Thomas; Beckmann, Markus; Bengsch, Michael; Feige, Irene; Schober, Markus (Springer International Publishing : Imprint: Springer, 2023)
XXVIII, 285 p. 18 illus.